A New Method To Reposition the Displaced Articular Disc For a Patient With Comminuted Condylar Fracture. Issue 4 (June 2019) - Yan, Guangqi; Zhou, Qing; Yang, Mingliang
Abstract : Background: Repositioning the displaced articular disc is the key procedure that prevents ankylosis of the temporomandibular mandibular joint (TMJ) in the treatment of patients with comminuted condylar fractures. The conventional procedure performed clinically is to use two anchors and sutures to reposition the displaced articular disc. Therefore, this paper introduces a new and economical method to reposition the articular disc without metallic implantation materials. Clinical presentation: A 60-year-old male patient who had fainted suddenly 3 days before came to our hospital to complain of pain of the bilateral TMJ areas and limited mouth opening. Clinical examination revealed severe restriction of mouth opening and the disappearance of bilateral condylar movements. Preoperational 3-dimensional computed tomography (3-DCT) indicated bilateral intracapsular comminuted fractures of the mandibular condyles. The patient was operated in a bilateral preauricular approach for repositioning of the bilateral articular discs and removal of the fracture fragments. Instead of repositioning the displaced disc with anchors, we designed a method to use sutures to stabilize the TMJ disc and to assess the disc's position using a magnetic resonance imaging (MRI) scan when following up. There were no severe complications during the operation. Results of an MRI scan 1 month after operation showed that post-operation articular discs kept their normal position, the mouth opening and the lateral and protrusive movements of the mandible recovered when followed up for 3 months. Conclusion: The method of using sutures to reposition and stabilize the articular disc for a patient with comminuted fractures is effective. There is great significance not only for patients with comminuted condylar fractures but for treatment of TMJ dysfunction especially for patients with high psychological pressure who persist in requiring the removal of metallic anchors although there are no clinical symptoms. Abstract : Supplemental Digital Content is available in the text